Translation commentary re-examined in the eyes of translator educators at British universities - Yi-yi Shih, Claire (The Journal of Specialised Translation, 2018)
Translation commentary is often used as an assessment method in translation degrees. In spite of this, relatively little attention has been paid to it empirically. This paper, on the one hand, proposes Kolb's experiential learning cycle (2014) to conceptualise the use of translation commentary in translator education; on the other hand, it reports on an interview study detailing translator educators' perception of translation commentary and their institutional practice of using translation commentary as an assessment method. Interview results show that translation commentary is perceived to be a hybrid of both an academic essay and reflective narrative. Its assessment is found to be linked to the hybridity. The true value of translation commentary probably lies in its conjunctive nature of transcending the boundary among knowledge, skill, theory and practice.